Comparative and Experimental Studies on the Genes Altered by Chronic Hypoxia in Human Brain Microendothelial Cells - Mata-Greenwood, Eugenia; Goyal, Dipali; Goyal, Ravi (Frontiers in Physiology, 2017)
Abstract Background: Hypoxia inducible factor 1 alpha (HIF1A) is a master regulator of acute hypoxia; however, with chronic hypoxia, HIF1A levels return to the normoxic levels. Importantly, the genes that are involved in the cell survival and viability under chronic hypoxia are not known. Therefore, we tested the hypothesis that chronic hypoxia leads to the upregulation of a core group of genes with associated changes in the promoter DNA methylation that mediates the cell survival under hypoxia. Results: We examined the effect of chronic hypoxia (3 days; 0.5% oxygen) on human brain micro endothelial cells viability and apoptosis. Hypoxia caused a significant reduction in cell viability and an increase in apoptosis. Next, we examined chronic hypoxia associated changes in transcriptome and genome-wide promoter methylation. The data obtained was compared with 16 other microarray studies on chronic hypoxia. Nine genes were altered in response to chronic hypoxia in all 17 studies. Interestingly, HIF1A was not altered with chronic hypoxia in any of the studies. Furthermore, we compared our data to three other studies that identified HIF-responsive genes by various approaches. Only two genes were found to be HIF dependent. We silenced each of these 9 genes using CRISPR/Cas9 system. Downregulation of EGLN3 significantly increased the cell death under chronic hypoxia, whereas downregulation of ERO1L, ENO2, adrenomedullin, and spag4 reduced the cell death under hypoxia. Conclusions: We provide a core group of genes that regulates cellular acclimatization under chronic hypoxic stress, and most of them are HIF independent.